Desarrollo de un control PID para un sistema de almacenamiento de energía basado en supercapacitores mediante un Convertidor Dual Active Bridge (DAB). - Herrera Balseca, Karen Alejandra (2023)
This work focuses on the simulation of a double active bridge (DAB) converter applying a proportional, integral and derivative (PID) control strategy in open loop and closed loop during the charging and discharging process of the power system based on supercapacitors, controlling the voltage output when the converter works in a steady state to maintain a constant power transfer over a time interval.